Assessment of Black Carbon in University: Emphasis on Different Indoor Microenvironment, Infiltration Factor, and Exposure - Sholikin, Mohamad; Rosariawari, Firra; Jawwad, Muhammad Abdus Salam (Jurnal Serambi Engineering, 2025)
Black carbon (BC), a harmful air pollutant, poses significant risks to human health. As students spend most of their time indoors and a third in school, the educational environment deserves special attention; however, most previous research has focused on the assessment of the pollutant itself in the classroom. Therefore, this work aims to extend the characterisation of BC in universities by considering different indoor microenvironments, infiltration factors and estimating exposures for healthy children and adults. In this study, BC concentrations were measured in four room types: cafeteria, gym, office room and classroom. The average BC observed in the cafeteria (599 ng m-³), gymnasium (987 ng m-³), office (830 ng m-³) and classroom (548 ng m-³) were. Of these, the gymnasium had the highest mean concentration, consistent with its high indoor/outdoor (I/O) ratio of 1.11, indicating significant indoor sources of BC. Exposure levels correlated directly with BC concentrations, with adults having higher deposition rates compared to children. These results provide insights into the spatial variation of BC in indoor environments, with implications for air quality control and health risk assessment for occupants.